2022
DOI: 10.3390/curroncol29120780
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patients’ and Physicians’ Knowledge and Expectations Regarding Precision Oncology Tests

Abstract: (1) Background: As genomic testing is becoming a part of the mainstream oncology practice, it is vital to ensure that our patients fully understand the implications of these tests. This study aimed to compare the attitudes and expectations of cancer patients with those of their physicians regarding the role of biomarker testing in clinical decision making. (2) Methods: Two separate, complimentary, self-administered questionnaires for patients with cancer and their physicians, respectively, were collected in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Also, where specified, much of the available data were based on well-educated patients of European descent (or "non-Hispanic White"). 17,18,21,22,[26][27][28][29][30][31][32][33] Additionally, evaluation of populations in two review articles showed an underrepresentation of other ethnic and minority groups, which was also supported by author statements in these publications. 30,33,[35][36][37][38][39] Patients were interested in receiving information on different types of cBT results, especially those impacting their own and their children and relatives' health.…”
Section: Search Outcomesmentioning
confidence: 69%
See 4 more Smart Citations
“…Also, where specified, much of the available data were based on well-educated patients of European descent (or "non-Hispanic White"). 17,18,21,22,[26][27][28][29][30][31][32][33] Additionally, evaluation of populations in two review articles showed an underrepresentation of other ethnic and minority groups, which was also supported by author statements in these publications. 30,33,[35][36][37][38][39] Patients were interested in receiving information on different types of cBT results, especially those impacting their own and their children and relatives' health.…”
Section: Search Outcomesmentioning
confidence: 69%
“…Sixteen additional studies focused on general or post‐testing cBT‐related communication in either the clinical care or research context, whereby the distinction between the two was not always clear 12,17–22,26,28,31–33,36,37,47,48 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations